Define $f: V \times V \rightarrow \mathbb{K}$ ($\mathbb{K}$ field), by $f(u, v) = \langle u, Av\rangle$, any $u$, $v \in V$ and $A \in M(n, \mathbb{R})$ with $A^T = -A$, i.e., $A$ is skew-symmetric.

a) Prove $f$ is skew-symmetric.

b) Prove $f$ is symplectic if and only if $A$ is invertible.

c) Prove the item b) implies which $n$ must be even. If you can help me.

The item a), founded is:

$f$ is skew-symmetric if $f(u,v) = - f(v,u)$. Then $f(u,v) = \langle u, Av\rangle = \langle A^T u, v\rangle = \langle -Au, v\rangle = - \langle v, Au\rangle = - f(v,u)$.

But I don't understand the first step: Why $\langle u, Av\rangle = \langle A^T u, v\rangle$ ?

Help me, please.

Note: for b), $f$ is symplectic if $f$ is bilinear form with the propriety $f(u,v) = -f(v,u)$ and $\ker f = \{0\}$, where $\ker f = \{v \in V; f(u,v) = 0, \mbox{for any}\; u \in V\}$.

Note2: For matrices in bilinear forms, the only thing I saw is that if $V$ is a vector space of $n$ finite dimension, we can consider $f: V \times V \rightarrow \mathbb{K}$, with $f: \mathbb{K}^n \times \mathbb{K}^n \rightarrow \mathbb{K}$, by $(e_i, e_j) \mapsto f(e_i, e_j) = B_{ij}$ and then consider $\{e_1, e_2, \ldots, e_n\}$ basis of $\mathbb{K}^n$, $u = \sum u_ie_i$, $v=\sum v_je_j$, we obtain for a general bilinear form $f(u,v) = \displaystyle\sum_{i,j=1}^{n}u_iv_jB_{ij}$. But I can not understand the items b) and c) what I mentioned in the item a). Sorry if the question is very simple to you, but I found in search and can not solve it.


For (a) we wish to show that $$ \langle u,Av\rangle = \langle A^\top u,v\rangle $$ To do so, we compute \begin{align*} \langle u,Av\rangle &= \sum_{i=1}^n u_i[Av]_i \\ &= \sum_{i=1}^n u_i\sum_{j=1}^n A_{ij}v_j \\ &= \sum_{j=1}^nv_j\sum_{i=1}^nA_{ij}u_i \\ &= \sum_{j=1}^n v_j\sum_{i=1}^n A^\top_{ji}u_i \\ &= \sum_{j=1}^n v_j[A^\top u]_j \\ &= \sum_{j=1}^n [A^\top u]_j v_j \\ &= \langle A^\top u,v\rangle \end{align*}

Addendum: If we trust the formula $$ \langle x,y\rangle=x^\top y $$ then our identity is quite obvious. We have $$ \langle u, A\,v\rangle= u^\top (A\,v)=\left((A\,v)^\top u\right)^\top =\left((v^\top A^\top)u\right)^\top=(v^\top (A^\top\, u))^\top=(A^\top\,u)^\top v=\langle A^\top u,v\rangle $$

  • $\begingroup$ Thank you!! Got the item a) now. $\endgroup$ – Samuel Francisco Feb 27 '15 at 1:33

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.